Strategy to Develop The Halal Products and Tourism in Indonesia with The Anshar Market Concept - Syukriyana, Dzikriya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Indonesia as a country with the largest Muslim population has the potential to become the world's halal centre. The increase in demand for halal products is due to the increasing world Muslim population and demand among non-Muslim consumers. Strengthening the halal industry is one way to develop the Islamic economy and improve the welfare of the people in Indonesia. However, halal product assurance is not only sufficient through certification. Therefore, a more concrete strategy is still needed to increase public trust in halal products.This research is a qualitative research with a literature review approach. The type of data used is secondary data or data that has been processed. The analysis technique used is qualitative descriptive analysis, which analyses data, facts, and social phenomena that occur to draw a conclusion. A strategy that provides more halal guarantees to the community is needed, namely by emulating what the Prophet Muhammad did in Medina. Morals are one of the important factors in developing the halal industry. The concept of the Anshar market and the Prophet's Mosque can be developed as a strategy for developing halal products and tourism in Indonesia.